Intra-couple income distribution and subjective well-being: The moderating effect of gender norms - Gábor Hajdu; Tamás Hajdu (Hungarian Academy of Sciences, Institute of Economics, 2017)
This paper examines the relationship between intra-couple income distribution and subjective well-being, using nationally representative data from Hungary. We show that the association between the woman's relative income (the woman's share of the couple's total earnings) and life satisfaction is negative not only for men, but for women as well. Because we control for financial disadvantages on the individual and household level, as well as for socio-economic and job characteristics of the respondent and their partner, the result can be interpreted as the impact of traditional gender roles and the persistence of the traditional male breadwinner mentality. In addition, we show that gender norms moderate this negative association. Among those with low levels of traditional norms, the woman's relative income has no effect on life satisfaction, whereas among those who prefer traditional gender roles, the negative association is stronger. Our results suggest that conflicts between the gender norms and the social and economic reality reduce life satisfaction.
Keywords: I31; D10; J16; 330; intra-couple income distribution; life satisfaction; gender norms; relative income